2021
DOI: 10.1037/aca0000273
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the if, the when, and the what of the sublime: A survey and latent class analysis of incidence, emotions, and distinct varieties of personal sublime experiences.

Abstract: Sublime encounters provide a compelling example of the peaks of our shared emotional and cognitive experiences. For centuries, these have been a target for philosophy and, more recently, for psychology, with its renewed focus on profound or aesthetic events. The sublime has been theoretically connected to multiple contexts, from interactions with overpowering nature, to beauty, music, even interpersonal engagements, and to multiple emotions-danger, awe, pleasure, fear-often with diametrically opposing argument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 59 publications
(222 reference statements)
4
48
0
2
Order By: Relevance
“…The nature-based format resulted in significantly higher fear and positive affect compared to the art-based format. This could be explained in relation to the nature of the Burkean sublime as a mixed emotional feeling tinged with fear or sense of danger [ 13 , 15 , 29 ]. Results suggested that this last element was prevalent in the nature-based format, in line with Burkean theorization of the sublime [ 2 ] and with the empirical findings of Hur and coll [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature-based format resulted in significantly higher fear and positive affect compared to the art-based format. This could be explained in relation to the nature of the Burkean sublime as a mixed emotional feeling tinged with fear or sense of danger [ 13 , 15 , 29 ]. Results suggested that this last element was prevalent in the nature-based format, in line with Burkean theorization of the sublime [ 2 ] and with the empirical findings of Hur and coll [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…We compared the effects of a nature-based and an art-based format in terms of their relative impact on the subjective state of the sublime. Drawing on philosophical and psychological work on the sublime [ 2 , 16 , 29 ], we may expect nature-based elicitors to appear more threatening or to hold, at least, a blended or mixed emotional profile, as suggested mainly by Burke’s account [ 2 ]. Although an early study of the link between sublime and fear in artworks showed that fear predicted a feeling of the sublime [ 30 ], this has since been questioned by Hur and colleagues [ 16 ], who conclude that whether fear is a component of the sublime merits further study.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together these findings show that there is not a clear-cut association between ES and either positive or negative emotions, and that probably, following Pelowski et al (2019)'s suggestion, a positive and a negative variant of ES might exist. This would weaken the idea that the sublime is the dark side of awe, and more generally it puts pressure on option C (as well as on a specific reading of option D, as it will be made clear shortly).…”
Section: The Equivalence Between Awe and The Experience Of The Sublimementioning
confidence: 66%
“…Moreover, although in line with philosophical treatment of ES they expected to find activation in brain areas classically associated with the experience of fear and threat such as the amygdala and the insula, their results did not show any such activity. Pelowski et al (2019) investigated the cognitive-affective profile of ES in a large sample. They reported that the vast majority of reports (90.8%) could be classified under one category associated with positive emotions (e.g., pleasure).…”
Section: The Equivalence Between Awe and The Experience Of The Sublimementioning
confidence: 99%
“…As seen in the stimuli of Chirico et al (2017) as well as in other awe-focused studies, researchers incorporate quite "high intensity" stimuli to elicit this emotion, such as "vastness" or "being moved" (Pelowski et al, 2019). With the same argument in the background, Shiota et al (2007) suggested to elicit awe with stimuli such as music, art, or nature (in this case, massive natural experiences), due to its focus on cognitive functions.…”
Section: The Special Role Of Awementioning
confidence: 99%